Reflecting the changing face of America: Multiracials, racial classification, and American intermarriage - Joel Perlmann (Levy Economics Institute of Bard College, 1997)
On the United States' census form, American citizens are told they may list any ethnic ancestries with which they identify, but are instructed to mark one only in the question on race. Joel Perlmann asserts that it is in the public interest to allow people to declare themselves as having origins in more than one race. To do otherwise is to deny that interracial marriages exist. This denial distorts our understanding of race data whether we are discussing projections of the composition of the American population or the definition of racial and minority status involved in discrimination legislation, affirmative action, and hiring and firing practices. If racial barriers are to be broken down, racial intermarriage should be treated in the same way any other form of ethnic intermarriage is treated, while ensuring that civil rights legislation, which rests on racial classification and counts, is not hobbled by ambiguities.
Keywords: 330